The Effect of Company Size and Sustainability Reporting on Profitability with Good Corporate Governance as a Moderating Variable - Nanda Dwi Wahyu Bima Atmojo; Nandhiko Wahyu Mukti; Muhammad Akmal Baskoro; Arsyifa Maulidina; Bambang Subiyanto (International Journal of Education, Information Technology, and Others, 2026)
This study analyzes the effect of company size and Sustainability Reporting (SR) on Profitability (PR) with the Audit Committee (AC) as a moderating variable determined for Good Corporate Governance (GCG), in companies listed on the IDX80 Index on the IDX in 2020-2024, the research are tested using WarpPLS 8.0 as the statistical program. It was concluded that company size has a significant negative effect on profitability, while sustainability reporting and the moderating role of good corporate governance (GCG) are not significant with profitability